Frozen conflicts of Russia - Leitis, Kārlis (Riga Graduate School of Law, 2018)
The bachelor thesis contains legal analysis of Russian interventions in Ukraine, Georgia and Moldova from international law perspective. The analysis of the frozen conflicts from international relations perspective and the relationship between territorial integrity and people’s right to self-determination is analysed.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Political science::Peace and conflict research; Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Russian-Georgian military conflict; Russia-Ukraine conflict; Russia-Moldova conflict